You are on page 1of 8

Proof by Mathematical Induction

• PRINCIPLE OF MATHEMATICAL INDUCTION To


prove that P(n) is true for all
• positive integers n, where P(n) is a
propositional function, we complete two steps:
• BASIS STEP: We verify that P(1) is true.
• INDUCTIVE STEP: We show that the
conditional statement P(k) → P(k + 1) is true
for all positive integers k.
Show that if n is a positive integer, then

• Solution: Let P(n) be the proposition that the


sum of the first n positive integers,

• We must do two things to prove that P(n) is


true for n = 1, 2, 3, . . . .
• Namely,we must showthatP(1) is true and that
the conditional statementP(k) impliesP(k + 1)
• is true for k = 1, 2, 3, . . . .
• BASIS STEP: P(1) is true, because
• (The left-hand side of this equation is 1 .The
right-hand side is found by substituting 1 for n
in n(n + 1)/2.)
• INDUCTIVE STEP: For the inductive hypothesis
we assume that P(k) holds for an arbitrary
positive integer k. That is, we assume that

• Under this assumption, it must be shown that


P(k + 1) is true, namely, that
• is also true. When we add k + 1 to both sides
of the equation in P(k), we obtain

• This last equation shows that P(k + 1) is true


under the assumption that P(k) is true.
Principle of Mathematical Induction

Let P(n) be a predicate defined for integers n.


Suppose the following statements are true:
1. Basis step:
P(a) is true for some fixed aZ .
2. Inductive step: For all integers k ≥ a,
if P(k) is true then P(k+1) is true.
Then for all integers n ≥ a, P(n) is true.

6
Example: Sum of Odd Integers
 Proposition: 1 + 3 + … + (2n-1) = n2
for all integers n≥1.
 Proof (by induction):
1) Basis step:
The statement is true for n=1: 1=12 .
2) Inductive step:
Assume the statement is true for some k≥1
(inductive hypothesis) ,
show that it is true for k+1 .

7
Example: Sum of Odd Integers
 Proof (cont.):
The statement is true for k:
1+3+…+(2k-1) = k2 (1)
We need to show it for k+1:
1+3+…+(2(k+1)-1) = (k+1)2 (2)
Showing (2):
1+3+…+(2(k+1)-1) = 1+3+…+(2k+1) =
by (1)
1+3+…+(2k-1)+(2k+1) =
k2+(2k+1) = (k+1)2 .
We proved the basis and inductive steps,
so we conclude that the given statement true. ■

You might also like